Are caffeine's performance-enhancing effects partially driven by its bitter taste?. (October 2019) - Pickering, Craig
Abstract: Caffeine is a well-established ergogenic aid, with its performance-enhancing effects replicated across a variety of exercise types. Caffeine exerts its performance-benefits through many mechanisms, including acting as an adenosine receptor antagonist, and serving to reduce sensations of fatigue and pain. One potential mechanism that is currently underexplored is whether caffeine's bitter taste mediates some of its ergogenic effects, which is discussed in this article. Previous research has demonstrated that bitter tastants have the ability to enhance performance, and this effect is mediated by bitter taste receptors in the mouth and gastrointestinal tract. Additionally, the ability to detect bitter tastes is subject to individual variation, raising the potential that the demonstrated inter-individual response to a standardised caffeine dose is potentially driven by differences in taste response. Finally, it appears that some of caffeine's performance-enhancing effects are driven by expectancy. As bitter taste may serve as a signal that caffeine has been ingested, it is possible that some of the expectancy effects of caffeine ingestion are driven by its bitter taste. These aspects all have potentially important implications for future research, as well as for how athletes and coaches utilise caffeine around competition, both of which are explored in depth here.